Comparative Analysis Of Firewall and Honeypot in Network Security Systems: Systematic Literature Review - M. Hanif Khairullah; Ilham Vigo Alfat; Eva Kurnia Putri; Rifky Reza Rahman; Muhammad Ar Rafi Erlangga; Zaki Nuryanto (Pusat Penelitian dan Pengabdian Politeknik Negeri Tanah Laut, 2026)
Rapid advances in information and communication technology have led organizations to increasingly rely on computer networks as a means of exchanging data and providing digital services. However, this increased use of computer networks is also accompanied by increasingly complex cybersecurity threats, such as Distributed Denial of Service (DDoS) attacks, brute force attacks, malware, phishing, and unauthorized access to network systems. Various security mechanisms have been created to deal with these threats, including firewalls and honeypots. Firewalls function as the primary defense that regulates and filters network traffic based on certain security rules, while honeypots are decoy systems designed to attract, detect, and analyze attacker behavior. This study aims to analyze and compare firewall and honeypot technologies based on security effectiveness, attack detection capabilities, intrusion prevention, and configuration complexity using the Systematic Literature Review (SLR) method, with 36 published articles through the steps of identification, selection, quality evaluation, data extraction, and synthesis of results. Research findings indicate that firewalls are superior in preventing unauthorized access and enforcing network security policies, while honeypots are superior in detecting attack patterns, gathering threat information, and analyzing attacker behavior. Combining these two technologies has the potential to strengthen network defenses more comprehensively.